Potential antidepressant effects of a dietary supplement from Huáng qí and its complex in aged senescence-accelerated mouse prone-8 mice - Chou, Ming-Yu; Wong, Yue-Ching; Wang, Shih-Yi; Chi, Ching-Hsin; Wang, Teng-Hsu; Huang, Mao-Jung; Huang, Ping-Hsiu; Li, Po-Hsien; Wang, Ming-Fu (Frontiers in Nutrition, 2023)
Healthcare is an emerging industry with significant market potential in the 21 st century. Therefore, this study aimed to evaluate the benefits of tube feeding Huáng qí and its complexes for 8 weeks on 3-month-old senescence-accelerated mouse prone-8 (SAMP8) mice, 48 in total, randomly divided into 3 groups including control, Huáng qí extract [820 mg /kg Body weight (BW)/day], and Huáng qí complexes (6.2 mL /kg BW/day), where each group consisted of males (n = 8) and females (n = 8). Behavioral tests (locomotion test and aging score assessment on week 6, the single-trial passive avoidance test on week 7, and the active shuttle avoidance test on week 8) were conducted to evaluate the ability of the mice to learn and remember. In addition, after sacrificing the animals, the blood and organs were measured for antioxidant and aging bioactivities, including malondialdehyde (MDA) content and superoxide dismutase (SOD) activity and catalase activities (CAT), and the effects on promoting aging in SAMP8 mice were investigated. The findings showed that Huáng qí enhanced locomotor performance and had anti-aging effects, with positive effects on health, learning, and memory in SAMP-8 mice (p < 0.05), whether applied as a single agent (820 mg /kg BW/day) or as a complex (6.2 mL/kg BW/day) (p < 0.05).